The development of effective biomarkers for Alzheimer's disease: a review. (4th June 2012) - Henry, Mark S.; Passmore, Anthony P.; Todd, Stephen; McGuinness, Bernadette; Craig, David; Johnston, Janet A.
Abstract : Objective: There is a widely recognised need to develop effective Alzheimer's disease (AD) biomarkers to aid the development of disease‐modifying treatments, to facilitate early diagnosis and to improve clinical care. This overview aims to summarise the utility of key neuroimaging and cerebrospinal fluid (CSF) biomarkers for AD, before focusing on the latest efforts to identify informative blood biomarkers. Design: A literature search was performed using PubMed up to September 2011 for reviews and primary research studies of neuroimaging (magnetic resonance imaging, magnetic resonance spectroscopy, positron emission tomography and amyloid imaging), CSF and blood‐based (plasma, serum and platelet) biomarkers in AD and mild cognitive impairment. Citations within individual articles were examined to identify additional studies relevant to this review. Results: Evidence of AD biomarker potential was available for imaging techniques reflecting amyloid burden and neurodegeneration. Several CSF measures are promising, including 42 amino acid β ‐amyloid peptide (A β 42 ); total tau (T‐tau) protein, reflecting axonal damage; and phosphorylated tau (P‐tau), reflecting neurofibrillary tangle pathology. Studies of plasma A β have produced inferior diagnostic discrimination. Alternative plasma and platelet measures are described, which represent potential avenues for future research. Conclusions: Several imaging and CSF markers demonstrate utility in predicting AD progression and determining aetiology. These require standardisation before forming core elements of diagnostic criteria. The enormous potential available for identifying a minimally‐invasive, easily‐accessible blood measure as an effective AD biomarker currently remains unfulfilled. Copyright © 2012 John Wiley & Sons, Ltd.